Evidence-based skills in criminal justice : international research on supporting rehabilitation and desistance - Ugwudike, Pamela, 1969-; Raynor, Peter; Annison, Jill (Bristol, UK : Chicago, IL, USA : Policy Press, 2018)
'How can evidence-based skills and practices reduce re-offending, support desistance, and encourage service user engagement during supervision in criminal justice settings? How can those who work with service users in these settings apply these skills and practices? This book is the first to bring together international research on skills and practices in probation and youth justice, while exploring the wider contexts that affect their implementation in the public, private and voluntary sectors. Wide-ranging in scope, it also covers effective approaches to working with diverse groups such as ethnic minority service users, women and young people.'--
Includes bibliographical references and index.
Keywords: Criminals -- Rehabilitation; Evidence-based social work